Peran Sanggar Suara Perempuan dalam Pendampingan Sosial Terhadap Penyintas Kekerasan Seksual Di Kabupaten Timor Tengah Selatan - Lak'apu, Maria Sarlensi; Pareira, Mariana Ikun RD; Neonufa, Samrid (Education For All, 2025)
Sexual violence is any form of act or attempted act of sexual intercourse that occurs due to coercion, threats, persuasion, deception and pressure that makes the victim trapped in the situation. Sexual violence against women, especially adolescents, occurs because adolescence is a transitional period from childhood to adulthood which puts adolescents in an unstable state. This research uses qualitative research methods and a case study approach with data collection through observation, interviews, and documents. The results of this study are that the support services provided by SSP provide emotional support, counselling services, shelter services, legal assistance and education. SSP is a safe place for women to share their experiences and get help from counsellors who deal with issues of violence against women. The sources of information for this research are people who are directly involved in the mentoring process. The findings of this study will discuss the SSP programme in providing services to adolescent survivors of sexual violence, which includes 1) Stages of the mentoring process for survivors. 2) The challenges of mentoring in supporting survivors 3) The impact/benefits of mentoring for survivors after receiving services from SSP. The Sanggar Suara Perempuan (SSP) mentoring program for adolescent victims of sexual violence supports psychological recovery through trauma-based counselling and support.